Reliable electricity: The effects of system integration and cooperative measures to make it work - Simeon Hagspiel (Institute of Energy Economics at the University of Cologne (EWI), 2017)
We investigate the effects of system integration for reliability of supply in regional electricity systems along with cooperative measures to support it. Specifically, we set up a model to contrast the benefits from integration through statistical balancing (i.e., a positive externality) with the risk of cascading outages (a negative externality). The model is calibrated with a comprehensive dataset comprising 28 European countries on a high spatial and temporal resolution. We find that positive externalities from system integration prevail, and that cooperation is key to meet reliability targets efficiently. To enable efficient solutions in a non-marketed environment, we formulate the problem as a cooperative game and study different rules to allocate the positive and negative effects to individual countries. Strikingly, we find that without a mechanism, the integrated solution is unstable. In contrast, proper transfer payments can be found to make all countries better off in full integration, and the Nucleolus is identified as a particularly promising candidate. The rule could be used as a basis for compensation payments to support the successful integration and cooperation of electricity systems.
Keywords: C63; C71; D47; Q42; Q48; 330; Electricity; Reliability of supply; Generation adequacy; System integration; Cooperative game